A multicenter measurement of magnetization transfer ratio in normal white matter - Berry, Isabelle; Barker, Gareth J.; Barkhof, Frederik; Campi, Adriana; Dousset, Vincent; Franconi, Jean-Michel; Gass, Achim; Schreiber, Wolfgang; Miller, David H.; Tofts, Paul S. (Journal of magnetic resonance imaging, 1999)
To assess the importance of intercenter variations when measuring magnetization transfer ratio (MTR) in the brain, six European centers measured MTR in normal white matter. MTR ranged from 9 to 51 percent units (25 sequences). The effective flip angle of the saturating pulse divided by the pulse repetition time (ENRsat degrees/msec) was a good predictor of MTR (MTR = 3.25 ENRsat).J. Magn. Reson. Imaging 1999; 9:441-446. © 1999 Wiley-Liss, Inc.